Perbedaan Stres Akademik Antara Mahasiswa Tahun Awal dan Mahasiswa Tahun Akhir - Dony Darma Sagita; Wiwi Rhamadona (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
The purpose of this study was to determine and describe the differences stress between early and final year students in academics, This study used a quantitative approach with a comparative descriptive method, and the study population was students of Guidance and Counseling Study Program, Faculcity of Teacher Training and Education, University of Muhammadiyah Prof.Dr.Hamka. The sampling technique used was proportional stratified random sampling. The sample obtained was 192 students, consisting of 98 early year students and 94 final year students. The academic stress instrument adopted from Sagita et., all (2017) consist of 34 items using a likert scale. The data findings were analysed using the independent sample t-test calculation. The result show that: (1) the academic stress of early year students is in the low category, (2) the academic stress between early year students and final years students.